Log Jams at a Bridge with a Pier and a Bridge without Pier. (2015) - Rusyda, Muhammad Islamy
Abstract: A flume experiment was carried out in a rectangular flume in order to investigate interaction between two different model bridges and logs from the viewpoint of flood disaster prevention. Logs is assumed representative of flowing wood during floods. The model bridge with a pier and model bridge without pier were used as an obstruction in rivers. The bridge with a pier is an usual bridge in the Yabe River basin and the bridge without pier is an usual bridge in the Nayoshi River basin. The result reveal that a log jam at a model bridge is determined by shaded area of an obtruction in the channel. In addition, An empirical equation for predicting the volume of woody debris accumulations at bridges is proposed.